Frequency distribution of different joint slopes containing ceramic soil under seismic wave action - Wei, Zhengqi; Li, Xuanzhe; Cao, Haiqing; Wu, Tingyao (Frontiers in Earth Science, 2024)
The dynamic response characteristics of high and steep slopes under the action of earthquakes and blasting was focused on, especially the frequency distribution and propagation laws, which are crucial for slope stability assessment. Using stress wave theory as the theoretical basis and advanced FLAC3D numerical simulation technology, we systematically analyze the frequency response of slope under different joint conditions under seismic waves. The nonlinear characteristics of reflected P-wave coefficient and the significant sensitivity of joint to incident wave frequency are revealed when the Angle of incident P-wave changes. The results show that with the increase of the incidence Angle of the incident P-wave, the reflection coefficient of the reflected P-wave decreases slowly at first and then increases sharply to 1.0. The reflection coefficient of the wave at the joint is more sensitive to the frequency of the incident wave. In a biplanar rock mass, multiple reflections of waves between structural planes produce transmitted waves with different time differences.